2020
DOI: 10.24874/ijqr14.01-13
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Digital Product: Theory and Practice

Abstract: The purpose of the research is to develop the scientific and theoretical basis for measuring the quality of various digital products, determining this quality in modern Russia, and compiling recommendations for their management in the interests of their increase. The author performs differentiation of quality of various digital products and evaluation of the current quality of digital products in Russia and develops recommendations for increasing the quality of digital products in Russia. The author also devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Thus, it is known that traditional QM practices showed to be inefficient when applied in the context of complex processes [73]. Hence, some authors, such as Brown [39], Antony [74], Shin et al [75], among others, explore the future direction of the quality movement, which will have to take into account the quality of products manufactured [76] in the era of the digital economy [77,78], that is related to Industry 4.0 [31,[79][80][81][82][83], with a lot of influence on the future of employment [11].Thus, the direction of quality in the future is then explored by identifying a big number of questions that have probably a great impact on quality in most of the organizations. But according to others researchers, such as Liao et al [84], the main research directions of quality management and the current research efforts, allow us to disclose this state-of-the-art: if on the one hand, (1) the research directions that have already attracted more research efforts, such as, Reference Architecture and Standardization, Vertical and Horizontal Integration; and for on the other hand (2) the research directions that refer insufficient, or even the lack of skills research efforts, such as the End-to-End Digital Integration, or even Regulatory Framework.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is known that traditional QM practices showed to be inefficient when applied in the context of complex processes [73]. Hence, some authors, such as Brown [39], Antony [74], Shin et al [75], among others, explore the future direction of the quality movement, which will have to take into account the quality of products manufactured [76] in the era of the digital economy [77,78], that is related to Industry 4.0 [31,[79][80][81][82][83], with a lot of influence on the future of employment [11].Thus, the direction of quality in the future is then explored by identifying a big number of questions that have probably a great impact on quality in most of the organizations. But according to others researchers, such as Liao et al [84], the main research directions of quality management and the current research efforts, allow us to disclose this state-of-the-art: if on the one hand, (1) the research directions that have already attracted more research efforts, such as, Reference Architecture and Standardization, Vertical and Horizontal Integration; and for on the other hand (2) the research directions that refer insufficient, or even the lack of skills research efforts, such as the End-to-End Digital Integration, or even Regulatory Framework.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, these are industries with a high level of technology. Conversely, lower utilization rates for QMPs were identified in lower value-added industries (NACE 21,32,15). Based on these findings, it can be stated that there are some differences in the use of the scale of QMPs within the sector of manufacturing enterprises in Slovakia, while the difference factor is the size of the enterprise, the industry itself, and partly the technology and performance of the industry measured by valueadded.…”
Section: Resultsmentioning
confidence: 89%
“…Kuhn et al (2018) state that "Traditional QMPs showed to be inefficient when applied in the context of complex processes". The future direction of the quality movement will have to take into account the quality of products manufactured in the era of the digital economy (Popkova, 2019). Carnerud (2018) specifies trends in quality management, emphasizing the importance of some of them as more important (Six Sigma, ISO standards, Lean and Innovation) than others.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Осуществляемая параллельно с ESG-менеджментом практика использования цифровых технологий в менеджменте качества также подробно изучена и широко представлена в литературе (см., напр. : [Popkova, 2020;колядин, 2022;соловьев, Попкова, 2022;морозова, сметанина, сметанин, 2023a, b;Попкова, соловьев, сметанин, 2023]). среди преимуществ использования цифровых технологий в менеджменте качества -автоматизация контроля качества, в том числе с применением технологии машинного зрения.…”
Section: обзор литературыunclassified